2021
DOI: 10.1055/s-0041-1730901
|View full text |Cite
|
Sign up to set email alerts
|

Enteral Feeding for Children on Bilevel Positive Pressure Ventilation for Status Asthmaticus

Abstract: A retrospective data analysis was conducted to evaluate enteral nutrition practices for children admitted with status asthmaticus in a single-center pediatric intensive care unit. Of 406 charts, 315 were analyzed (63% male); 135 on bilevel positive airway pressure ventilation (BIPAP) and 180 on simple mask. Overall median age and weight were 6.0 (interquartile range [IQR]: 6.0) years and 24.8 (IQR: 20.8) kg, respectively. All children studied were on full feeds while still on BIPAP and simple mask; 99.3 and 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The incidence of respiratory and gastric complications in pediatric patients enterally fed while on NIV is variable [ 10 , 11 , 22 , 26 ]. Such differences may arise from the important variation in the definition of complication, the population studied, and the variable clinical practice between centers [ 3 , 10 , 15 , 22 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The incidence of respiratory and gastric complications in pediatric patients enterally fed while on NIV is variable [ 10 , 11 , 22 , 26 ]. Such differences may arise from the important variation in the definition of complication, the population studied, and the variable clinical practice between centers [ 3 , 10 , 15 , 22 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The findings here are similar to those described by Tume and colleagues in a cohort of children requiring NIV, predominantly HHFNC, where respiratory complications occurred in 12.3% of children and were mainly non-severe, with 1.5% of patients suffering from a pulmonary aspiration [ 24 ]. Another recent study including asthmatic patients on BiPAP showed no complications secondary to EN [ 26 ]. Studies investigating respiratory deteriorations with enteral nutrition evaluate for aspirations or surrogates for gastric intolerance such as vomiting or gastric residual volume.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations